Sarcoid heart disease. Issue 984 (4th October 2007) - Dubrey, Simon W; Bell, Alex; Mittal, Tarun K
Abstract : To this day the aetiology of sarcoidosis continues to elude definition. Partially as a consequence of this, little in the way of new therapies has evolved. The enigma of this condition is that, unusually for a disease with the potential for devastating consequences, many patients show spontaneous resolution and recover. Cardiac involvement can affect individuals of any age, gender or race and has a predilection for the conduction system of the heart. Heart involvement can also cause a dilated cardiomyopathy with consequent progressive heart failure. The most common presentation of this systemic disease is with pulmonary infiltration, but many cases will be asymptomatic and are detected on routine chest radiography revealing lymphadenopathy. Current advances lie in the newer methods of imaging and diagnosing this unusual heart disease. This review describes the pathology and diagnosis of this condition and the newer imaging techniques that have developed for determining cardiac involvement.